ANALISIS PERSEPSI DAN SIKAP PETANI TERHADAP ATRIBUT BENIH KOPI DI PROVINSI LAMPUNG - Hasibuan, Abdul Muis; Listyati, Dewi; Sudjarmoko, Bedy (Pusat Penelitian dan Pengembangan Perkebunan, 2013)
The adoption of coffee seeds by farmer strongly infulenced by their assessment on the availability of several factors. The objective of this study was to determine the perceptions and attitudes of farmers on the attributes of coffee seeds (superior and local seeds). The research was conducted in Lampung Province in September to November 2012 with a survey of 62 respondents. Data were analyzed by Fishbein multi-attribute analysis. The results showed that the resistance to pests and diseases was the most important attributes, followed by productivity. Meanwhile seed viability attributes was the least important. The attitude of farmers towards superior seeds more higher than the local seed. It encourages farmers to prefer the superior seed compared to local seeds, and results of the survey showed that 63.38% of respondents already use the superior seed.